Visceral manifestation of blackleg in animals - Natalia L (Jurnal Ilmu Ternak dan Veteriner, 2000)
Blackleg, an infectious disease caused by Clostridium chauvoei leads to sudden death in animals. Cases of blackleg in Bontang, East Kalimantan and Lampung recognized a different patterns of lesions produced by classical infection. It was called visceral blackleg. The classic form of the disease characterized by gross muscle lesions, while visceral manifestation of blackleg were found in this observation. The visceral manifestations of the disease is not commonly recognized. These two disease patterns caused by the same species of CI. chauvoei. The atypical lesions and laboratory findings characteristic of visceral manifestation of blackleg are described. In the group of animals in which outbreak is occuring, those affected are the individuals that are in the best physical condition. The relationship between physical condition and susceptibility to Cl. chauvoei infection need to be further investigated.   Key words: Blackleg, visceral type, Clostridium chauvoei